Counterfactual scenarios. A reflection on the Institutional Theory of art - Pla, Adrià Harillo [UNESP] (Universidad Catolica Luis Amigo, 2024)
Following the definition provided by Osvaldo Pessoa Jr., a Counterfactual Scenario would be a possible situation that did not take place, as a future possibility at some point in the past. This concept is not new. In fact, it has a significant presence in fields such as analytical philosophy, economics, experimental sciences, or psychology. The aim of this text is to present, through theoretical and conceptual rigor and the inductive method, a reflection not derived from research. This reflection is the importance of the relationship between counterfactual scenarios and the art world from an institutional perspective. The initial observation that supports this text is that, in an age in which anything can be art, and yet not everything is, the reasons why something could have been art, but was not, are of great importance to understand the basis of its economic and cultural value and to deepen our linguistic categories of the present. In this case, art.
ESCENARIOS CONTRAFÁCTICOS. UNA REFLEXIÓN SOBRE LA TEORÍA INSTITUCIONAL DEL ARTE
Keywords: Artworld; Contemporary art; Counterfactual scenarios; Historical revisionism; Institutional theory; Possible worlds